Comparison of adding tocilizumab to methotrexate with switching to tocilizumab in patients with rheumatoid arthritis with inadequate response to methotrexate: 52-week results from a prospective, randomised, controlled study (SURPRISE study). Issue 11 (5th January 2016) - Kaneko, Yuko; Atsumi, Tatsuya; Tanaka, Yoshiya; Inoo, Masayuki; Kobayashi-Haraoka, Hitomi; Amano, Koichi; Miyata, Masayuki; Murakawa, Yohko; Yasuoka, Hidekata; Hirata, Shintaro; Nagasawa, Hayato; Tanaka, Eiichi; et al.
Abstract : Objective: To compare the efficacy and safety between tocilizumab added to methotrexate and tocilizumab switched from methotrexate in patients with active rheumatoid arthritis (RA). Methods: This is a 2-year randomised, controlled study. RA patients with moderate or high disease activity despite methotrexate were randomly assigned either to tocilizumab added to methotrexate (add-on) or tocilizumab switched from methotrexate (switch). The primary endpoint was the DAS28 remission rate at week 24. Secondary objectives included other clinical efficacy indices, radiological outcomes assessed with the van der Heijde-modified total Sharp scoring system (mTSS), and safety. Results: Of 223 randomised patients, 83% completed 52 weeks. DAS28 remission rates at week 24 were 70% for add-on and 55% for switch (p=0.02), but they became comparable at week 52 (72% vs 70%, p=0.86). Structural remission rates (mTSS≤0.5) at week 52 were not different (66% vs 64%, p=0.92). However, clinically relevant radiographic progression rates (CRRP; mTSS≥3) tended to be higher with the switch than with the add-on (15% vs 7%, p=0.07). Radiographic progression in the CRRP patients was larger with the switch than with the add-on (9.0/year vs 5.0/year, p=0.04). The difference in the mean C-reactive protein of the CRRP patients was significant for the first 24 weeks (1.56 vs 0.49, p=0.001) but not for the following 28 weeks (0.10 vs 0.04, p=0.1). Overall safety was preferable in the switch group. Conclusions: In RA patients with inadequate response to methotrexate, tocilizumab added to methotrexate more rapidly suppressed inflammation than tocilizumab switched from methotrexate, leading to superior clinical efficacy and prevention of joint destruction. Trial registration number: NCT01120366.